Effect of Neurofibrillary Tangles on Behavioural Flexibility in Rats: Animal Models for Fronto-Temporal Dementia and Alzheimer’s Disease - Sriram, Pallavi; Morrissey, Mark; Tanninen, Stephanie; Maal-Bared, Geith; Klein, Ronald L..; Takehara-Nishiuchi, Kaori (The Meducator, 2013)
Neurofibrillary tangles (NFTs) are aggregations of abnormal tau protein, which are implicated in neurodegenerative diseases such as behavioural-variant frontotemporal dementia (bvFTD) and Alzheimer’s disease (AD). NFTs are prominent in the prefrontal and entorhinal cortices in early-stage bvFTD and AD, respectively. We modeled this site-specific neurodegeneration in rats via microinjection of a viral vector to express an excess of mutated tau protein in these target areas. We then examined the impact of this somatic gene transfer on performance in a behavioural flexibility task. The rats were initially trained to find food rewards in a plus maze using a place strategy: to always go to the same place in the environment, i.e., north or south. Subsequently, they switched to a response strategy: to always make the same body response, i.e., turn right or left. Rats made a total of six switches between place and response strategies, and their acquisition and retention of each switch was measured and compared to controls. We found that bvFTD model rats could acquire the place strategy, but were impaired when acquiring the response strategy. AD model rats were impaired in acquiring both strategies. Despite differences in ability to acquire strategies, there were no impairments in retention of either strategy for both groups. Together, these findings suggest that patterns of performance on a behavioural flexibility paradigm can differentiate between animal models of early bvFTD and AD. Future research can use these findings to screen novel candidate drugs, and study mechanisms underlying AD and bvFTD.